Virus-mealybug relationship in the transmission of piper yellow mottle virus: Virus-mealybug relationship - Malavika, P; Lijisha, A; Bhat, A I (Journal of Spices and Aromatic Crops, 2023)
In the current study, the piper yellow mottle virus (PYMoV)-mealybug (Ferrisia virgata) relationship in the transmission of PYMoV in black pepper was determined. The mealybug F. virgata collected from healthy black pepper plants was reared on a pumpkin in the laboratory and used to determine the acquisition access period (AAP), retention period (RP) and inoculation access period (IAP) for the transmission of PYMoV. The crude extract isolated from black pepper plants and mealybugs were tested through PCR using PYMoV-specific primers. The study determined 30 min, 8 h, and 30 min as the AAP, RP, and IAP respectively, indicating the semipersistent type of transmission of PYMoV.